Determinants of perceived patient benefit in a longitudinal cohort study of patients with psoriasis and atopic dermatitis - Gloria-Beatrice Wintermann; Susanne Abraham; Eva M. J. Peters; Stefan Beissert; Kerstin Weidner (Scientific Reports)
Abstract The Dermatology Life Quality Index (DLQI) should be used to assess treatment success in psoriasis (PSO). However, the DLQI does not assess the importance and achievement of treatment goals. The Patient Benefit Index (PBI) is a questionnaire that takes both into account. Currently, there is insufficient knowledge about the modulating variables of the PBI and whether it can complement the assessment of the DLQI. In a longitudinal cohort study, 82 patients with PSO were assessed before and up to sixteen weeks after a new treatment episode. The PBI was compared with patients with atopic dermatitis (AD) (n = 61). The effects of gender, age, type of therapy, improvement in body surface area (BSA), anxiety/depression, DLQI and individual coping were assessed. “Getting better skin quickly” was most important in PSO. Improved BSA, anxiety/depression, DLQI, male gender and initiation of biological therapy had the most positive effects. Partial mediation was found for the reduction of anxiety/depression and improved coping. The PBI may be considered an appropriate outcome measure of treatment success in PSO, complementing the DLQI. Patients with clinically relevant anxiety/depression and inadequate coping should be offered adjuvant psychosomatic treatment.